Transformative conservation of ecosystems. (4th March 2022) - Fougères, Dorian; Jones, Mike; McElwee, Pamela D.; Andrade, Angela; Edwards, Stephen R.
Abstract : Non-technical summary: Many conservation initiatives call for 'transformative change' to counter biodiversity loss, climate change, and injustice. The term connotes fundamental, broad, and durable changes to human relationships with nature. However, if oversimplified or overcomplicated, or not focused enough on power and the political action necessary for change, associated initiatives can perpetuate or exacerbate existing crises. This article aims to help practitioners deliberately catalyze and steer transformation processes. It provides a theoretically and practically grounded definition of 'transformative conservation', along with six strategic, interlocking recommendations. These cover systems pedagogy, political mobilization, inner transformation, as well as planning, action, and continual adjustment. Technical summary: Calls for 'transformative change' point to the fundamental reorganization necessary for global conservation initiatives to stem ecological catastrophe. However, the concept risks being oversimplified or overcomplicated, and focusing too little on power and the political action necessary for change. Accordingly, its intersection with contemporary biodiversity and climate change mitigation initiatives needs explicit deliberation and clarification. This article advances the praxis of 'transformative conservation' as both (1) a desired process that rethinks the relationships between individuals, society, and nature, and restructures systems accordingly, and (2) a desired outcome that conserves biodiversity while justly transitioning to net zero emission economies and securing the sustainable and regenerative use of natural resources. It first reviews criticisms of area-based conservation targets, natural climate solutions, and nature-based solutions that are framed as transformative, including issues of ecological integrity, livelihoods, gender, equity, growth, power, participation, knowledge, and governance. It then substantiates six strategic recommendations designed to help practitioners deliberately steer transformation processes. These include taking a systems approach; partnering with political movements to achieve equitable and just transformation; linking societal with personal ('inner') transformation; updating how we plan; facilitating shifts from diagnosis and planning to action; and improving our ability to adjust to transformation as it occurs. Social media summary: Curious about stemming the global biodiversity and climate crises? Browse this article on transformative conservation!